KINERJA EFISIENSI BANK BERSTRATIFIKASI SESUAI DENGAN VISI ARSITEKTUR PERBANKAN INDONESIA - Sari Yuniarti (Jurnal Keuangan dan Perbankan, 2008)
This research was aimed to know the relative effeciency levels of banks andstratification suitable with the vision of Indonesia Banking Architecture. In the vision, bankcategorized as much as the core capital owned by the bank.Thus, in 2010 there would be bankscategorized as BPR, focus bank, national and international bank. The samples in this researchwere 30 go public banks in Indonesia stock exchange while the data was taken from 2004 to2007. By using Data Envelopment Analysis, it could be known that banks categorized focusand national had efficiency level which was relative the same. Based on this research, it couldbe concluded that banks with little core capital (Rp100 million Rp10 quintillion) had efficiencyability which was as good as the banks with more core capital (more than Rp 10 quintillion)